Follow-up survey of patients with occupational asthma. (20th April 2020) - Feary, J; Cannon, J; Fitzgerald, B; Szram, J; Schofield, S; Cullinan, P
Abstract: Background: Occupational asthma (OA) is often associated with a poor prognosis and the impact of a diagnosis on an individual's career and income can be significant. Aims: We sought to understand the consequences of a diagnosis of OA to patients attending our clinic. Methods: Using a postal questionnaire, we surveyed all patients attending our specialist occupational lung disease clinic 1 year after having received a diagnosis of OA due to a sensitizer ( n = 125). We enquired about their current health and employment status and impact of their diagnosis on various aspects of their life. Additional information was collected by review of clinical records. Results: We received responses from 71 (57%) patients; 77% were referred by an occupational health (OH) provider. The median duration of symptoms prior to referral was 18 months (interquartile range (IQR) 8–48). At 1 year, 79% respondents were no longer exposed to the causal agent. Whilst the unexposed patients reported an improvement in symptoms compared with those still exposed (82% versus 53%; P = 0.023), they had poorer outcomes in terms of career, income and how they felt treated by their employer; particularly those not currently employed. Almost all (>90%) of those still employed had been referred by an OH provider compared with 56% of those currently unemployed ( P = 0.002)x. Conclusions: The negative impact of OA on people's careers, livelihood and quality of life should not be underestimated. However, with early detection and specialist care, the prognosis is often good and particularly so for those with access to occupational health.